KEDELAI HITAM (Glycine soja) TERHIDROLISIS SEBAGAI SUMBER FLAVONOID TOTAL - Muammar Fawwaz; Diana Syam Muliadi; A. Muflihunna (Jurnal Fitofarmaka Indonesia, 2017)
Flavonoids are natural phenolic compounds found in almost all plants that have potential as antioxidants. Based on previous research, stating that black soybeans contain compounds of flavonoids. This analysis aims to establish the levels of total flavonoids on ethanol extract of black soybean hydrolyzed. Determination of total flavonoid levels of ethanol extract of black soybean hydrolyzed has been made with UV-Vis spectrophotometry method. Black soybean hydrolyzed using HCl and extracted using ethanol 70%. The extracts obtained were analyzed qualitative by the method of coloring reaction and quantitative analysis using UV-Vis spectrophotometer, where quercetin is used as a reference standard. Measurements were performed at maximum wavelength of 444.45 nm. The research showed the average level of total flavonoids is 11.83 mgQE / g extract or 1,163 %. In conclusion extract of black soybean hydrolyzed rich of total flavonoids, and it is related to the activity as antioxidant.